New and interesting Peritelini of the Western Mediterranean fauna. XX. A novel Meira (Jacquelin du Val, 1852) species from the Ligurian Alps - Pierotti, Helio; Fink, Thomas (Zootaxa, 2013)
Meira diottii, nov.sp. from the Ligurian Alps is described. Relevant anatomical characters are detailed and illustrated with drawings and photography. Characteristic sensilla on the penis are identified and illustrated with scanning electron microscopy. Relationships with other Meira species are proposed.